Business cycle synchronization across US states - Aguiar-Conraria, Luís (2017)
We use wavelet analysis to conclude that individual U.S. states' business cycles are very well synchronized. We also find evidence of a strong and significant correlation between business cycle dissimilitudes and the distance between each pair of states, consistent to gravity type mechanisms where distance affects trade. Trade, in turn, increases business cycle synchronization, while a higher degree of industry specialization is associated with a higher dissimilitude of the state cycle with the aggregate economy. Finally, there is evidence that business cycle dissimilitudes have been decreasing with time, consistent with the previous findings coupled with the idea that information and communications technology make distances smaller.